2016
DOI: 10.12659/msm.898883
|View full text |Cite
|
Sign up to set email alerts
|

MiR-206 Suppresses the Progression of Coronary Artery Disease by Modulating Vascular Endothelial Growth Factor (VEGF) Expression

Abstract: BackgroundWe investigated whether microRNA-206 (miR-206) is abnormally expressed in patients with coronary artery disease (CAD). The potential mechanism by which miR-206 may regulate CAD progression was also studied.Material/MethodsA total of 78 CAD patients in the case group and 65 subjects in the control group were enrolled in this study so that the correlation between miR-206 and CAD could be accurately determined. Serum total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 44 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…114 A study suggested that miR-206 might be an innovative biomarker and suppress the progression of CAD by reducing VEGF. 115 Thus, miR-206 may be a robust target for the inhibition of the growth and angiogenesis of various cancers through modulating multifaceted targets. However, further studies should be performed for understanding the mechanisms of miR-206 in angiogenesis.…”
Section: Mir-206mentioning
confidence: 99%
“…114 A study suggested that miR-206 might be an innovative biomarker and suppress the progression of CAD by reducing VEGF. 115 Thus, miR-206 may be a robust target for the inhibition of the growth and angiogenesis of various cancers through modulating multifaceted targets. However, further studies should be performed for understanding the mechanisms of miR-206 in angiogenesis.…”
Section: Mir-206mentioning
confidence: 99%
“…Among these miRNAs, miR-206 was identified to have protective effects on the development of coronary artery disease and cancers. 15,16 In particular, studies revealed that miR-206 participated in the progression of glioma by functioning as a tumor inhibitor to regulate cellular biological processes, and decreased miR-206 expression was associated with poor prognosis in glioma. [17][18][19] Further, miR-206 knockdown was shown to protect human embryonic stem cells (hESCs) against propofol-induced cell apoptosis, thereby inhibiting neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, miR-206 was elevated the in plasma of COPD patients and was corrected with COPD severity as measured by FEV1% predicted. 16 However, the role of miR-206 in COPD and the underlying molecular mechanisms still remain unclear. 16 However, the role of miR-206 in COPD and the underlying molecular mechanisms still remain unclear.…”
Section: Introductionmentioning
confidence: 99%